Effects of thermal and oxygen conditions during development on cell size in the common rough woodlice Porcellio scaber - Antoł, Andrzej (John Wiley and Sons Inc., 2020)

(untitled) (Ecol Evol)
During development, cells may adjust their size to balance between the tissue metabolic demand and the oxygen and resource supply: Small cells may effectively absorb oxygen and nutrients, but the relatively large area of the plasma membrane requires costly maintenance. Consequently, warm and hypoxic environments should favor ectotherms with small cells to meet increased metabolic demand by oxygen supply. To test these predictions, we compared cell size (hindgut epithelium, hepatopancreas B cells, ommatidia) in common rough woodlice (Porcellio scaber) that were developed under four developmental conditions designated by two temperatures (15 or 22°C) and two air O(2) concentrations (10% or 22%). To test whether small‐cell woodlice cope better under increased metabolic demand, the CO(2) production of each woodlouse was measured under cold, normoxic conditions and under warm, hypoxic conditions, and the magnitude of metabolic increase (MMI) was calculated. Cell sizes were highly intercorrelated, indicative of organism‐wide mechanisms of cell cycle control. Cell size differences among woodlice were largely linked with body size changes (larger cells in larger woodlice) and to a lesser degree with oxygen conditions (development of smaller cells under hypoxia), but not with temperature. Developmental conditions did not affect MMI, and contrary to predictions, large woodlice with large cells showed higher MMI than small woodlice with small cells. We also observed complex patterns of sexual difference in the size of hepatopancreatic cells and the size and number of ommatidia, which are indicative of sex differences in reproductive biology. We conclude that existing theories about the adaptiveness of cell size do not satisfactorily explain the patterns in cell size and metabolic performance observed here in P. scaber. Thus, future studies addressing physiological effects of cell size variance should simultaneously consider different organismal elements that can be involved in sustaining the metabolic demands of tissue, such as the characteristics of gas‐exchange organs and O(2)‐binding proteins.